Towards modular compilers for effects - Day, Laurence; Hutton, Graham (Springer, 2012)
Compilers are traditionally factorised into a number of separate phases, such as parsing, type checking, code generation, etc. However, there is another potential factorisation that has received comparatively little attention: the treatment of separate language features, such as mutable state, input/output, exceptions, concurrency and so forth. In this article we focus on the problem of modular compilation, in which the aim is to develop compilers for separate language features independently, which can then be combined as required. We summarise our progress to date, issues that have arisen, and further work